RECYCLED POLYETHYLENE BONDED PARTICLE BOARD FROM PULPED AND UNPULPED GMELINA ARBOREA SAW DUST WASTES - Ogunsile, B. O.; Saheed, R. (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
Particle boards were prepared from saw dust wastes obtained from Gmelina aborea using polyethylene as binder. The boards were produced under three different compositional variables, namely: particles sizes (1 µm, 1.5 µm and 2 µm), densities (450kg/m3, 550 kg/m3 and 650 kg/m3) and mixing ratios ofsaw dust to polyethylene (30:70, 40:60 and 50:50). Part of the saw dust samples were chemically modified by pulping with caustic soda at 110oC and the effect of modification was examined on the physical and mechanical properties of the particle boards. The results showed that the chemically modified particle boards showed improved resistance to swelling and water absorption while a decrease was observed in the values of the modulus of rupture and elasticity.